Mindfulness Strategies for Metacognitive Skills Training in Special Education: The Role of Virtual Reality - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalampos (Technium Social Sciences Journal, 2022)
The purpose of the current review study is to provide representative evidence regarding the effectiveness of mindfulness training strategies on the development of metacognitive skills for people with special education needs. In addition, we explore the role of virtual reality in the efficacy of mindfulness interventions among people with learning disabilities, neurodevelopmental disorders, intellectual disabilities, and behavioral disorders. In addition, we present innovative mindfulness training strategies, appropriate for metacognitive skills training in special education. Finally, we seek the features that possibly make virtual reality a fertile ground for the implementation of mindfulness training. The results showed that mindfulness training improves the metacognitive skills needed for the inclusion of people with disabilities. Virtual reality constitutes an effective assistive technology that can facilitate mindfulness training in various contexts, accelerating positive outcomes in mental and physical health, academic performance, and well-being.